2010
DOI: 10.1073/pnas.0912127107
|View full text |Cite
|
Sign up to set email alerts
|

Observations of aminium salts in atmospheric nanoparticles and possible climatic implications

Abstract: We present laboratory studies and field observations that explore the role of aminium salt formation in atmospheric nanoparticle growth. These measurements were performed using the Thermal Desorption Chemical Ionization Mass Spectrometer (TDCIMS) and Ultrafine Hygroscopicity Tandem Differential Mobility Analyzers. Laboratory measurements of alkylammonium-carboxylate salt nanoparticles show that these particles exhibit lower volatilities and only slightly lower hygroscopicities than ammonium sulfate nanoparticl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
465
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 432 publications
(491 citation statements)
references
References 46 publications
(31 reference statements)
25
465
0
1
Order By: Relevance
“…A more comprehensive soil and litter SOA composition data set needs to be generated to determine whether or not the dominant SOA precursors are constant over time or if there are bursts in emissions not measured here that may contribute to variability. Amines have been suggested as potential aerosol precursors from soil and litter previously, 42,43 and would not have been detectable with the analytical equipment used here. Neither the PTR-MS nor the GC-MS-FID measured sesquiterpenes in significant amounts, but these compounds are known to have high losses in sampling lines 44,45 and previous work has indicated that aerosol yields can be very sensitive to the presence of sesquiterpenes.…”
Section: Environmental Science and Technologymentioning
confidence: 93%
“…A more comprehensive soil and litter SOA composition data set needs to be generated to determine whether or not the dominant SOA precursors are constant over time or if there are bursts in emissions not measured here that may contribute to variability. Amines have been suggested as potential aerosol precursors from soil and litter previously, 42,43 and would not have been detectable with the analytical equipment used here. Neither the PTR-MS nor the GC-MS-FID measured sesquiterpenes in significant amounts, but these compounds are known to have high losses in sampling lines 44,45 and previous work has indicated that aerosol yields can be very sensitive to the presence of sesquiterpenes.…”
Section: Environmental Science and Technologymentioning
confidence: 93%
“…For example, aliphatic amines contributed 23% to the NPF events at a remote forested site in Hyytiala, Finland in March, 2006 and 47% to that at an urban site in Tecamac, Mexico in April, 2007. 12 Amines observed in Marshall Field Site, Colorado (2007), 13 North Boulder, Colorado (2009), and Atlanta, Georgia (2009) 14 have also been confirmed to play the same role in NPF events. 12 In laboratory studies, NPF was observed when amines were added into a smog chamber or flow tube reactor containing a certain concentration of nitric acid, 15 sulfuric acid, 16 or methanesulfonic acid (MSA).…”
Section: ■ Introductionmentioning
confidence: 93%
“…12 Amines observed in Marshall Field Site, Colorado (2007), 13 North Boulder, Colorado (2009), and Atlanta, Georgia (2009) 14 have also been confirmed to play the same role in NPF events. 12 In laboratory studies, NPF was observed when amines were added into a smog chamber or flow tube reactor containing a certain concentration of nitric acid, 15 sulfuric acid, 16 or methanesulfonic acid (MSA). 17,18 Density functional theory (DFT) calculations indicated that amine molecules act as cluster stabilizers for nucleation precursors, 19,20 and therefore promote nuclei formation.…”
Section: ■ Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…in the continental boundary layer have been reported 17,19,20 , suggesting that sulphuric acid-amine nucleation is likely to be an important atmospheric process. However, atmospheric observations indicate both the presence 10,11,16 and the absence 22 of a significant amine fraction in newly formed particles, which suggests considerable variability of ambient amine levels. Although amines are volatile vapours, our measurements show that sulphate particles constitute an almost perfect sink (negligible evaporation).…”
mentioning
confidence: 99%